Neue maßgeschneiderte Vakuumlösungen: Innovationen im Bereich der Vakuumtechnik am GSI Helmholtzzentrum für Schwerionenforschung. (December 2015) - Engert, Tobias; Surowiec, Alicja; Krause, Jörg; Mosel, Günter; Günther, Niklas
Abstract : New customized vacuum solutions The importance of working under (high) vacuum conditions increases constantly in various applications and technology areas. The GSI Helmholtzzentrum für Schwerionenforschung in Darmstadt has also been continuously working on new optimized customized solutions in this area for decades. As the largest Hessian research organization the GSI has also developed some important inventions in the field of vacuum technology. These are highly vacuum‐tight encapsulated cases and their production, a new laser welding technique for particle‐free encapsulation and an improved method for applying getter layers, in particular for NEG (non‐evaporating getter) layers.